1996
DOI: 10.2466/pms.1996.83.3f.1211
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in WAIS–R Age-Corrected Scaled Scores

Abstract: Analyses of variance were conducted on WAIS–R age-corrected scaled scores and global intelligence standard scores with gender as the independent variable. Significant differences between men and women were found on three subtests, Information, Arithmetic, and Block Design. For all three significant differences, the 115 men scored higher than the 115 women ( M age = 34.8; Range 16 to 71 years). The implications of these findings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…This dissociation may reflect testosterone deficiency in the KS group only. Higher testosterone levels in males may be related to increased male performance in visual-spatial tasks involving mental rotation, spatial perception, spatial visualization [Arceneaux et al, 1996].…”
Section: Visual Spatial Functionmentioning
confidence: 99%
“…This dissociation may reflect testosterone deficiency in the KS group only. Higher testosterone levels in males may be related to increased male performance in visual-spatial tasks involving mental rotation, spatial perception, spatial visualization [Arceneaux et al, 1996].…”
Section: Visual Spatial Functionmentioning
confidence: 99%
“…How older and younger individuals develop sex role identities and experience life events and passages obviously vary across cohorts or historical time. For example, Arceneaux et al [8] found evidence supporting age moderation of gender differences based on longitudinal data from WAIS/WAIS-R subtests. More specifically, the observed gender differences were moderated by age for some skills, particularly, those requiring spatial abilities.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Consistent with Mitrushina et al (2005), the averages were weighted by sample size. Larger samples were given proportion- Arceneaux et al (1996) 230 Wiens et al (1993) 302 Ivnik et al (1992) 512…”
Section: Meta-analysis Norm Construction and Comparison To Quota Normingmentioning
confidence: 99%